The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1210/en.2017-00348
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid X Receptor Activation Alters the Chromatin Landscape To Commit Mesenchymal Stem Cells to the Adipose Lineage

Abstract: Developmental exposure to environmental factors has been linked to obesity risk later in life. Nuclear receptors are molecular sensors that play critical roles during development and, as such, are prime candidates to explain the developmental programming of disease risk by environmental chemicals. We have previously characterized the obesogen tributyltin (TBT), which activates the nuclear receptors peroxisome proliferator-activated receptor γ (PPARγ) and retinoid X receptor (RXR) to increase adiposity in mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
76
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 94 publications
3
76
0
1
Order By: Relevance
“…Enhanced adipogenesis as an adverse effect of exposure to MDCs is often accompanied by changes in epigenetic gene regulation as previously found [14][15][16][17][18][19][20]. For example, prenatal exposure to the MDC tributyltin (TBT) increases the number of adipocytes in mice offspring [21].…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Enhanced adipogenesis as an adverse effect of exposure to MDCs is often accompanied by changes in epigenetic gene regulation as previously found [14][15][16][17][18][19][20]. For example, prenatal exposure to the MDC tributyltin (TBT) increases the number of adipocytes in mice offspring [21].…”
mentioning
confidence: 81%
“…Additionally, prenatal exposure to TBT leads to a change in adipogenesis in the F4 generation, which is linked to changes in sperm chromatin structures. Of importance, activation of the retinoid X receptor (RXR) by TBT or a RXR-selective agonist (IRX4204) showed a reduced expression of EZH2 [20]. As a consequence, redistribution and an overall decrease of H3K27me3 were observed, especially close to genes involved in adipogenesis [20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently shown that TBT and other chemicals that activate RXR commit MSCs to the adipose lineage by activating RXR, but not PPARγ. TBT and pharmacological RXR agonists derepress genes important for adipogenic commitment by decreasing deposition of the repressive chromatin mark, histone 3 lysine 27 trimethyl (H3K27 me3 ) in the promoters and regulatory regions of these genes, leading to increased expression of their mRNAs . Therefore, it is likely that other RXR activators (these are collectively called “rexinoids”) such as the fungicide fludioxonil or the surfactant SPAN‐80 will produce similar effects.…”
Section: Obesogens Reprogram Stem Cell Fatementioning
confidence: 99%
“…TBT and pharmacological RXR agonists derepress genes important for adipogenic commitment by decreasing deposition of the repressive chromatin mark, histone 3 lysine 27 trimethyl (H3K27 me3 ) in the promoters and regulatory regions of these genes, leading to increased expression of their mRNAs. 92 Therefore, it is likely that other RXR activators (these are collectively called "rexinoids") such as the fungicide fludioxonil or the surfactant SPAN-80 will produce similar effects. Intriguingly, a variety of other fungicides with widely divergent structures, including flusilazole, zoxamide and quinoxyfen, are candidate obesogens, in vitro.…”
Section: Stem Cell Fatementioning
confidence: 99%